Evolutionary Patterns of Flexible Automation and Performance: A Longitudinal Study - Boyer, Kenneth K. (Management Science, 1999)
This study presents a longitudinal analysis of patterns of investment in advanced manufacturing technologies (AMT) and financial performance. Investments in AMT from 112 manufacturing plants in the metal-working industries are examined. Data were collected via a mail survey administered to 202 plants in 1994, and readministered to 112 of the same plants in 1996. This study seeks to fill a void in the area of technology management, which is comprised primarily of cross-sectional studies that do not address the dynamic nature of investments in technology. Four major conclusions are drawn from the data. First, several individual technologies have higher investments in 1996 than in 1994. In particular, electronic mail has the largest increase in investment, a finding that suggests that manufacturing firms are finding ways to take advantage of the exploding potential of electronic communication. Our second conclusion is that plants invest in technology in an incremental fashion over time rather than using an all-or-nothing approach. Plants with low investments follow one of three technology strategies as their investments in AMTs evolve: (1) continued low investment, (2) investment primarily in design-based technologies, or (3) equalized investment in design, manufacturing, and administrative AMTs. Third, analysis of the degree of manufacturing involvement in developing business strategy indicates that plants that have a more proactive role for manufacturing invest greater resources in AMTs. Finally, while AMT investment was not positively associated with performance in a cross-sectional analysis, longitudinal analysis of data collected two years later does reveal a relationship. In short, the analysis supports the proposition that there is a lag between initial investment and resulting performance improvements.